Poética do desc-arte: fotografia e meio ambiente em Santa Maria - Zofoli, Jane Andiara Soares (2020)
Desc-Arte is a research in Visual Arts, whose realization process combines photography, video and installation, and aims to question the discard through artistic creation, in order to sensitize through the photographic reframed and to verify how it is discard out in Santa Maria RS. The transmutation of objects without art in art has existed since Marcel Duchamp, and has become an unavoidable reality in the contemporary practice of art. Therefore, Desc-Arte proposes a work that questions and sensitizes, in the expectation of provoking the awareness of a sustainable practice in relation to what is consumed and rejects, particularly, in this locality. Art, because it is aesthetic, is also political and lends itself to artistic practice and theoretical formalization about disposal. In this sense, centralizing the present work as a means of resignifying the gaze from the discard opportunistizes the transmutation of this object without art to the art that this project sustains. For that, re-signifying the discarded objects through the look of the image as a poetry that transforms makes the insignificance given to the discard a means of raising awareness of the recurring problem in today's society. To this end, works by renowned artists and authors, through which the issue of disposal in Santa Maria was addressed, and in authors of photography and art who contribute to clarify the issues support it. Questioning what it means to give visibility to what seems insignificant to many and to see how the public power of this locality treats the problem were goals followed with intensity. Sustaining the path is the question: would art not contain the necessary contents capable of sensitizing and raising awareness of entire layers of society that discards and, at the same time, becomes a victim of its own acts?